Enfermedad de Ménière: caso clínico y revisión de la literatura - Pereira C., Nicolás; Espinoza G., Carolina; Concha P., Raimundo; Walker J. , Katherine (Revista Hospital Clínico Universidad de Chile, 2008)
Ménière’s disease is characterized by spontaneous attacks of vertigo, fluctuating sensorineural hearing loss, aural fullness, and tinnitus. The pathofisiology involves distortion of the membranous labyrinth with the formation of endolymphatic hydrops. Initial management of Ménière’s disease can involve a low-salt diet and a diuretic. Treatment with intratympanic injection of gentamicin can be beneficial when vertigo persists despite optimal medical management. Recent studies have shown that gentamicin reduces vestibular function in the treated ear, and is not always necessary to forgo the remaining hearing of the affected ear to achieve control of vertigo.